A priority multi-channel coordination MAC protocol in roadside unit-assisted vehicular networks. (11th September 2019) - Qaashah, Shamsan M.; Ramadan, Rabie A.; Fayek, Magda B.
This paper presents a priority-based RSU assisted multi-channel coordination MAC protocol (PRAMC) for vehicular ad hoc network (VANET). The paper provides the priority for vehicles in the RSU polling list in order to poll vehicles according to their priorities. So, vehicles can transmit the high priority and important messages before low priority ones. A vehicle includes its priority with the association request frame. After RSU receives the association request, it adds the vehicle to a polling list according to its priority. RSU in this situation is responsible for control and safety messages broadcasted and non-safety application. The proposed protocol in this paper is an enhancement to the previous RAMC MAC protocol where no priority messages were considered. Our simulation results show high throughput for non-safety applications as compared to previous works. In addition, the results achieve high delivery ratios for different priorities of emergency warning messages (EWMs) and status safety messages in different traffic densities.